Jamming Skins that Control System Rigidity from the Surface. (24th September 2020) - Shah, Dylan S.; Yang, Ellen J.; Yuen, Michelle C.; Huang, Evelyn C.; Kramer‐Bottiglio, Rebecca
Abstract: Numerous animals adapt their stiffness during natural motions to increase efficiency or environmental adaptability. For example, octopuses stiffen their tentacles to increase efficiency during reaching, and several species adjust their leg stiffness to maintain stability when running across varied terrain. Inspired by nature, variable‐stiffness machines can switch between rigid and soft states. However, existing variable‐stiffness systems are usually purpose‐built for a particular application and lack universal adaptability. Here, reconfigurable stiffness‐changing skins that can stretch and fold to create 3D structures or attach to the surface of objects to influence their rigidity are presented. These "jamming skins" employ vacuum‐powered jamming of interleaved, discrete planar elements, enabling 2D stretchability of the skin in its soft state. Stretching allows jamming skins to be reversibly shaped into load‐bearing, functional tools on‐demand. Additionally, they can be attached to host structures with complex curvatures, such as robot arms and portions of the human body, to provide support or create a mold. We also show how multiple skins can work together to modify the workspace of a continuum robot by creating instantaneous joints. Jamming skins thus serve as a reconfigurable approach to creating tools and adapting structural rigidity on‐demand. Abstract : Jamming skins transform between flexible, stretchable sheets and rigid, inextensible exoskeletons upon application and removal of vacuum pressure. By combining stretchability with variable‐stiffness properties, jamming skins can be formed into 3D shapes that contain compound curvatures and locked on‐demand. Jamming skins present a means for creating structures in resource‐limited environments and increasing the adaptability of soft robots and wearable systems.